Challenging behaviors in medical students: clarification of observations of professors - Hossein Karimi Moonaghi; Ali Emadzadeh; Raheleh GharibNavaz; Mostafa Rad; Hakimeh Sabeghi; Houra AshrafiFard; Eshagh Ildarabadi (Tabriz University of Medical Sciences, 2020)
Background: Incivility or challenging behaviors in the scientific environment are so harmful that they cannot be neglected. Therefore, these behaviors should be addressed promptly and effectively. The aim of this study was to identify challenging behaviors from other behaviors and evaluate the severity of these behaviors from the viewpoint of university professors in medical students. Methods: This descriptive cross-sectional study was performed on a sample of 110 faculty members in Faculty of Medicine of Mashhad University of Medical Sciences. To identify challenging behaviors from other behaviors, the majority (>50%) was considered. Also, to determine the challenging intensity of each behavior, behaviors that had higher scores were regarded as very high challenging behaviors. Results: Based on the review of external and internal resources and the viewpoints of professors,32 behaviors were prepared in the form of a checklist for the faculty members to identify the challenge and severity of it. Behaviors such as student insolence, disturbance of class order, and non-respect of rules, as well as disruptive behavior with professors were recognized as the most challenging behaviors. Regarding the intensity of the student incivility, the disruptive behavior with professors, the non-customary jokes, the disruptive behavior with students, and the lack of compliance with the charter of patient rights were considered as very high incivility. Conclusion: Students' challenging behaviors interferes in their own learning, others' learning,staff as well as other individuals' rights, and order and security of educational environment.Professors and instructors ought to identify these behaviors and manage them.